Foreign direct investment:localization and institutional determinants - Leitão, Nuno Carlos (2011)
This article examines the foreign direct investment (FDI) in Portugal, i.e why foreign companies are located in Portugal. The compression of the determinants of FDI is important to take decisions on economic policy. The determinants of the location were used as market size, labour cost, taxes and economic stability. Beyond these were introduced two institutional variables the impact of globalization and corruption on FDI. The study applies a panel data approach (Fixed Effects and GMM system estimator). The results show that the market size and lobalization has a positive impact on FDI. he corruption has a negative impact on investor decisions. Wages, inflation and taxes are also statistically significant.